Effect of Axial Impact Loading On Energy Absorption Capability of Thin-Walled Structures in Automotive Application - MOHD AMIN, AIMAN NAIM (2017)
This study seeks to analyse the energy absorption and crushing behaviour of square thin-walled aluminium structures with the addition of different shapes of stiffeners internally by exposing them to axial quasi-static loading. The aspects of energy absorption analysed in these structures are specific energy absorption (SEA), mean crush force and initial maximum force. The means of getting those results are by performing numerical simulation by using ABAQUS, a finite element analysis software. The results showed that with the application of internal stiffener, the energy absorption capacity increases significantly. As for the different shapes of stiffener, the one with the most energy absorption capability compared to the others is the I-shape stiffener with 58% increase compared to the reference tube. This study conclude that the addition of internal stiffener can greatly increase the energy absorption in energy absorbers and thus reduce the impact of collision during crash.